37.3k views
2 votes
Solve the variable in the following equation: 5 + h = 11 − 2h

A. h = −1

B. h = 2

C. h = 5

D. h = 9

User Tipsy
by
5.1k points

2 Answers

1 vote

Answer:

B) h=2

Explanation:

5+h=11-2h

5+h-(-2h)=11

5+h+2h=11

5+3h=11

3h=11-5

3h=6

h=6/3

h=2

User Jsbisht
by
4.8k points
3 votes

Answer: B. h = 2

Explanation:

Given

5 + h = 11 - 2h

Add 2h on both sides

5 + h + 2h = 11 - 2h + 2h

5 + 3h = 11

Subtract 5 on both sides

5 + 3h - 5 = 11 - 5

3h = 6

Divide both sides by 3

3h / 3 = 6 / 3

h = 2

Hope this helps!! :)

Please let me know if you have any questions

User Paritosh Mahale
by
5.2k points